(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
This paper analyses the discourse of HIV and AIDS in the Nyanja speech community of Zambia. Specifically the paper critically analyses the concepts that this speech community uses to refer to the pandemic so as to try and unravel the people’s perceptions about the pandemic as embodied in these concepts. The paper posits that for HIV and AIDS information education and communication programmes to yield positive results, health communicators need to be aware of such conceptualisations as they have a lot to reveal about the people’s attitudes towards the pandemic that could have a bearing on their health conduct and uptake of HIV and AIDS information.